Out of the inkwell Max Fleischer and the animation revolution - Fleischer, Richard (Univ. Press of Kentucky, 2005)
Max Fleischer (1883-1972) was for years considered Walt Disney's only real rival in the world of cartoon animation. The man behind the creation of such legendary characters as Betty Boop and the animation of Popeye the Sailor and Superman, Fleischer asserted himself as a major player in the development of Hollywood entertainment. While deeply engaged with his characters, Fleischer also sought ways to improve his art through technical innovation. In the 1920s and 1930s, Fleischer created many patented inventions and introduced new special effects such as startling combinations of live action and animation, as well as a musical series involving jazz artists such as Cab Calloway and Louis Armstrong. In spite of its great popularity and success, however, the studio was abruptly closed in 1942. The animated cartoon industry was shocked, and the event went unexplained for many years. Now, Max's son Richard has at last solved the mystery of the shuttering of Fleischer Studios.--From publisher description.
Includes bibliographical references and index
Keywords: Fleischer, Max -- 1883-1972; Animatiefilms; Cartoons; Animators -- United States -- Biography; Animationsfilm; USA; Biografie